The Effectiveness of Non-Digital Interactive Spinning Wheel Media in Improving Arabic Learning Outcomes at Madrasah Aliyah - Yulanda Ilda; Musli; Mustar; Dina Chabib Uluum; Almu Padol; Mohamad Hussin (Al-Muyassar: Journal of Arabic Education, 2026)
Although previous studies have examined the use of spinning wheel media and digital instructional media in language learning, limited research has investigated the effectiveness of non-digital interactive spinning wheel media in Arabic language learning at the Madrasah Aliyah level, particularly in schools with limited technological facilities. This study aimed to examine the effectiveness of non-digital interactive spinning wheel media in improving students' Arabic learning outcomes at Madrasah Aliyah As'ad Jambi. The study employed a quantitative approach using a quasi-experimental non-equivalent control group design. The participants consisted of 66 students divided into an experimental group and a control group. Data were collected through pre-tests and post-tests and analyzed using the Mann–Whitney U test with SPSS software. The results revealed a significant difference between the learning outcomes of students in the experimental and control groups after the treatment (U = 274.00, Z = –3.54, p < .001). Students in the experimental group achieved higher learning outcomes than those in the control group. These findings indicate that non-digital interactive spinning wheel media can effectively support Arabic language learning and improve students' learning outcomes. This study contributes to the development of interactive and game-based Arabic language learning by demonstrating that effective instructional innovation can be implemented without relying on digital technology, particularly in educational settings with limited technological resources.